ANALISIS TINGKAT KEBUGARAN JASMANI DAN KEPERCAYAAN DIRI SISWA SEKOLAH MENENGAH PERTAMA NEGERI 30 PADANG - Rafid, Muhammad; Hardiansyah, Sefri; Erianti; Sepriadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the suboptimal implementation of Physical Education, Sports, and Health (PJOK) learning at State Junior High School 30 Padang, which is suspected to be influenced by the students' physical fitness and self-confidence levels. This study aims to analyze the physical fitness and self-confidence levels of students at the school. The method used was descriptive quantitative research with a population of 626 students from grades VII, VIII, and IX. Sampling was conducted using cluster random sampling technique, resulting in 64 students from classes VII A and VIII D as research subjects. The instruments used were the Indonesian Student Fitness Test (TKSI) Phase D and a self-confidence questionnaire. The results showed that the students' physical fitness level was in the